Raku: the spiritual aesthetic / Khairul Nizan Mohd Aris - Mohd Aris, Khairul Nizan (Universiti Teknologi MARA, Perak, 2016)
Unlike conventional ceramic firing approaches, which may take several days to complete, Raku is a method where work is rapidly (often under a hour in duration) fired and removed from the kiln when glowing hot. Raku has become popular amongst contemporary artists/potters internationally since it was introduced to the West in 1940s. Historically, Raku referred to the spiritual, religious, philosophical, ceremonial and functional characteristics of a specific style.